Nondegradation of fecal cholesterol in subjects at high risk for cancer of the large intestine. - Lipkin, M; Reddy, B S; Weisburger, J; Schechter, L (The Journal of Clinical Investigation, 1981)
In previous studies subjects with familial polyposis, the autosomal dominant disease leading to colon cancer, excreted higher levels of fecal cholesterol than normal subjects, with decreased conversion to degradation products. Findings suggested fecal cholesterol degradation as a marker of hereditary predisposition to colon cancer. Current measurements now have shown that affected individuals and asymptomatic progeny in a second population group with inherited predisposition to colon cancer are low converters of fecal cholesterol. The latter group consisted of highly colon cancer prone families without polyposis, in which patterns of inheritance similar to the autosomal dominant pattern of familial polyposis were observed. 24-h stool collections were obtained from 72 subjects who consumed mixed western diets. Mean percent degradation of fecal cholesterol to coprostanol, coprostanone, cholestanol, and cholestanone revealed significant decreases in fecal cholesterol conversion in affected and asymptomatic subjects in colon cancer prone families without polyposis (P < 0.001) compared to controls. This is in addition to those with familial polyposis (P < 0.001), and extends this marker of colon cancer susceptibility to a second population group with hereditary predisposition to colonic neoplasia.